The Effect of Bone and Analytical Methods on the Assessment of Bone Mineralization Response to Dietary Phosphorus, Phytase, and Vitamin D in Nursery Pigs - Hadley R. Williams; Taylor E. Chin; Jordan T. Gebhardt; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jon R. Bergstrom; Michael C. Rahe; Christopher L Siepker; Panchan Sitthicharoenchai; Steve M. Ensley (Kansas Agricultural Experiment Station Research Reports, 2022)
Three hundred-fifty pigs (initially 26.2 ± 1.23 lb) were used to evaluate the effects of bone and analytical methods on the assessment of bone mineralization response to dietary P and vitamin D in nursery pigs. Pens of pigs (5 or 6 pigs/pen) were randomized to 6 dietary treatments in a randomized complete block design with 10 pens per treatment. Treatments were formulated to have varying levels of P, phytase, and vitamin D to provide differences in bone characteristics. After feeding diets for 28 d, eight pigs per treatment were euthanized for bone, blood, and urine analysis. The response to treatment for bone density and ash was dependent upon the bone analyzed (density × bone interaction,P= 0.044; non-defatted bone ash × bone interaction,P= 0.060; defatted bone ash × bone interaction,P= 0.068). Pigs fed 0.19% STTD P had decreased (P<0.05) bone density and ash (non-defatted and defatted) for all bones compared to 0.44% STTD P, with 0.33% STTD P generally intermediate or similar to 0.44% STTD P. Pigs fed 0.44% STTD P with no vitamin D had greater (P<0.05) non-defatted fibula ash compared to all treatments other than 0.44% STTD P with added HyD. Pigs fed the three diets with 0.44% STTD P had greater (P<0.05) defatted 2nd rib ash compared to pigs fed 0.19% STTD P or 0.33% STTD P with no phytase. In summary, bone density and ash responses varied depending on the bone analyzed. Differences in bone density and ash in response to P and vitamin D were most apparent with fibulas and 2nd ribs. The difference between bone ash procedures was more apparent than the differences between treatments. For histopathology, 10th ribs were more sensitive than 2nd ribs or fibulas for detection of lesions.
Keywords: bone mineralization; growth performance; nursery pigs